From Finite Body to Infinite Body: Body Crisis and Response in the Post-human Era - Hao WANG (Yixue yu zhexue)
The concept of the body has undergone significant changes in the post-human era, transitioning from the human body to the post-human body. The post-human body mainly includes four forms: the primitive body which resembles the traditional human body, the enhanced body that undergoes human enhancement and transformation, the virtual body constructed by virtual information technology, and the non-human body expanded by multiple entities. The post-human body has triggered and exacerbated privacy and security crises, ethical and legal crises, socioeconomic crises, creative destruction crises, social control crises, and human nature loss crises. Addressing the body crises of the post-human era requires a shift in technological perspectives, a transformation of technological ethics, a redirection of technological approaches, an improvement in technological capabilities, and an optimization of technological structures.